Induksi Kalus dan Regenerasi Beberapa Genotipe Gandum (Triticum aestivum L.) secara In Vitro - Atmitri Sisharmini; Aniversari Apriana; Sustiprijatno Sustiprijatno (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2010)
Callus Induction and In Vitro Plant Regeneration ofWheat Genotypes (Triticum aestivum L.). AtmitriSisharmini, Aniversari Apriana, and Sustiprijatno. Developmentof a reliable in vitro plant regeneration procedure forwheat is a prerequisite for its improvement by genetic transformation.The purpose of this study was to obtain methodsof callus induction and regeneration of wheat genotypes.This experiment was conducted at ICABIOGRAD. Immatureembryos from four wheat genotypes, ie Perdix, Naxos Wew,Combi and Fasan were used to induce callus formation andregeneration rate of callus. For the preparation of callusinduction medium, MS-L7 basal medium was supplementedwith combination of growth regulators 2,4 dichlorophenoxyacetic acid (2,4-D) and 4-amino-3,5,6-trichloropicolinic acid(picloram). While, plant regeneration medium was preparedusing MS basal medium supplemented with combination ofthree growth regulators i.e. IAA, BAP and kinetin. The resultsshowed that genotype, in vitro culture medium and growthregulators played a dominant role in callus induction andplantlet regeneration. All the 4 genotypes responded positivelyto callus induction, however, variability was observednot only among the genotypes but also within callusinduction medium used. The best induction medium wasthe MS-L7 basal medium supplemented with combination ofphytohormon 4 mg/l 2,4-D + 2 mg/l picloram (GIK-3) whichshowed 100% callus induction frequency. Whereas, the bestregeneration medium was shown by MS basal medium withcombination of phytohormon 1.5 mg/l BAP dan 0.5 mg/lkinetin (RG3). Regarding plant regeneration, Perdix was themost responsive genotype to be regenerated with regenerationfrequency of 57.33%. The successfully acclimatizedplanlets in greenhouse were obtained from Perdix andNaxos Wew genotypes. These results will potentially facilitategenetic transformation research of wheat in Indonesia.